Negative Pressure Wound Therapy in Maxillofacial Applications - Adam J. Mellott; David S. Zamierowski; Brian T. Andrews (Dentistry Journal, 2016)
Negative pressure wound therapy has greatly advanced the field of wound healing for nearly two decades, by providing a robust surgical adjunct technique for accelerating wound closure in acute and chronic wounds. However, the application of negative pressure wound therapy in maxillofacial applications has been relatively under utilized as a result of the physical articulations and contours of the head and neck that make it challenging to obtain an airtight seal for different negative pressure wound therapy systems. Adapting negative pressure wound therapies for maxillofacial applications could yield significant enhancement of wound closure in maxillofacial applications. The current review summarizes the basic science underlying negative pressure wound therapy, as well as specific maxillofacial procedures that could benefit from negative pressure wound therapy.